Evaluating microbiological safety and associated handling practices of butchery-sold meat in Nairobi, Kenya - Koech, Patricia C.; Ogutu, Winnie A.; Ochieng, Linnet; Grace, Delia; Gitao, G.; Bebora, L.; Korir, Max; Mutua, Florence; Moodley, Arshnee (Frontiers Media, 2024)
Introduction: Approximately 70% of diarrheal cases in Kenya are attributed to ingestion of contaminated food and water and costs an estimated $ 1 billion USD due to morbidity and cost of treatment. This study aimed to assess the levels of microbiological contamination of meat sold in selected butcheries in Nairobi and the handling practices of butcher shop attendants.